Preferences and barriers for continuing professional development among dental practitioners in the twin cities of Hubli-Dharwad, India - Prajna Pramod Nayak; K V.V Prasad; C Jyothi; G S Roopa; Ranganath Sanga (Wolters Kluwer Medknow Publications, 2015)
Introduction: Advances in the field of dentistry is occurring at an exponential rate, and there is an immense pressure and challenge for the dentist to keep up with it to remain competent across the full spectrum of dental profession. Aim: To assess the frequency of attending the continuing professional development (CPD) courses as well as to assess the preferences and barriers for CPD among dental practitioners in Hubli-Dharwad, India. Materials and Methods: A self-administered questionnaire inquired on the frequency of attending CPD courses, and three questions on preferences and barriers for the same among 112 practitioners. Pearson's Chi-square test was used to find any association with gender and qualification with dependent variables. Results: Consent for the study was given by 92.9% practicing dentists. The mean age was 32.3 years. A majority of practitioners (45.2%) said that they attended CDE courses at least once in 6 months, 32.7% attended at least once in a year, and 22.1% attended rarely or never. A majority of dentists preferred esthetic dentistry. Most preferred methods for CPD courses were hands-on treatment on live patients and hands-on in clinically simulated situations. Lack of time was perceived as the most important barrier. Conclusions: A little less than half of the practitioners attended CPD courses once in 6 months with a substantial number attending very rarely or never. Most of them preferred esthetic dentistry and hands-on courses and lack of time was the most important barrier for attending CPD courses by Hubli-Dharwad dentists.